Campo escalar complexo num cenário de Randall-Sundrum - Viana, Marcio Gomes (2016)
In this work is analysed how is the behavior of the complex scalar field in the Randall- Sundrum RS scenery. The RS model is a model of extra dimension, that solves satisfactorily the problem of the Higgs hierarchy. The problem is related to the big discrepancy between the gravitational and eletroweak scales of mass. The obtained results are based in a not factorable geometry of the Anti-de-Sitter type. We will do a review about general relativity and spacetime anti-de-sitter. We will see the construction of the models RS-I and RS-II, as well how the calculus of conections, through the Christoffel symbol, Ricci tensor, Ricci scalar and Einsteins tensor. Finally, we study the localization of the charge and current of the complex field in a brane